Bisecting N-Acetylglucosamine Structures Inhibit Hypoxia-Induced Epithelial-Mesenchymal Transition in Breast Cancer Cells - Tan, Zengqi; Wang, Chenxing; Li, Xiang; Guan, Feng (Frontiers in Physiology, 2018)
The epithelial-mesenchymal transition (EMT) process plays a key role in many biological processes, including tissue fibrosis, metastatic diseases, and cancer progression. EMT can be induced by certain factors, notably hypoxia, in the tumor microenvironment. Aberrant levels of certain N-glycans is associated with cancer progression. We used an integrated strategy (mass spectrometry in combination with lectin microarray analysis) to elucidate aberrant glycosylation in a hypoxia-induced EMT model using breast cancer cell lines MCF7 and MDA-MB-231. The model showed reduced levels of bisecting GlcNAc structures, and downregulated expression of the corresponding glycosyltransferase MGAT3. MGAT3 overexpression in MCF7 suppressed cell migration, proliferation, colony formation, expression of EMT markers, and AKT signaling pathway, whereas MGAT3 knockdown (shRNA silencing) had opposite effects. Our findings clearly demonstrate the functional role (and effects of dysregulation) of bisecting GlcNAc structures in hypoxia-induced EMT, and provide a useful basis for further detailed studies of physiological functions of these structures in breast cancer.